2011
DOI: 10.1002/jccs.201190017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Urease Inhibition Studies of Barbituric and Thiobarbituric Acid Derived Sulphonamides

Abstract: Various novel barbituric and thiobarbituric acid derived sulphonamides were synthesized in excellent yield via three components single pot reaction; and these were screened for in vitro urease inhibition studies against jack bean urease. The compounds 1‐7 were found to exhibit a low to moderate activity whereas compounds 8‐14 showed a significant activity (88.3‐99.9% inhibition determined at 500 μM concentration). Structures of the synthesized compounds were confirmed by 1H‐NMR, 13C‐NMR, mass spectrometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…In contrast to antibacterial agent, the antiviral drug should have (X δ--Y δ-) pharmacophore site with respect of some architectural parameters (dihedral angle = 0-10 degree and distance d x-y = 3-3.5 Å). [33][34][35][36][37][38][39] This can be applied for all compounds described here ( Figure 5). …”
Section: 1 Petra Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to antibacterial agent, the antiviral drug should have (X δ--Y δ-) pharmacophore site with respect of some architectural parameters (dihedral angle = 0-10 degree and distance d x-y = 3-3.5 Å). [33][34][35][36][37][38][39] This can be applied for all compounds described here ( Figure 5). …”
Section: 1 Petra Analysismentioning
confidence: 99%
“…Molecular Polar Surface Area PSA is calculated as a sum of fragment contributions. [33][34][35][36][37][38][39] O-, N-and Scentered polar fragments are considered. PSA has been shown to be a very good descriptor characterizing drug absorption, including intestinal absorption, bioavailability, Caco-2 permeability and blood-brain barrier penetration.…”
Section: Molinspiration Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some are used for the treatment of psychiatric disorders such as anxiety and epilepsy by posing effects on motor and sensory functions 5,6 and are also reported as bactericidal agent 3,4,7 . Previously we have reported and identified various pharmacophores responsible for potent activity of barbiturate/thiobarbiturate nucleus via molecular modeling studies [8][9][10][11] . It is evident that the imide or b-amino a, b-unsaturated amide functionality is the basic structural moiety in these compounds which has multidimensional array of interaction sites resulting in either potential urease inhibitors (PUI), potential antibacterial (PAB), antifungal Inhibitors (PAF) and potential kinase inhibitors (PKI; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Akhtar et al have synthesized 3-substituted-4-amino-5-thioxo-1H-4H-1,2,4-triazoles derivatives showing their urease inhibition activity 12 . Rauf et al have reported the synthesis and urease inhibition activity of barbituric and thiobarbituric acid derivatives 13 . More recently, Khan et al also reported arylidene barbiturates as urease inhibitors 14 .…”
Section: Introductionmentioning
confidence: 99%